PREPARATION OF SINGLE-CHAIN METHYL METHACRYLATE COPOLYMERS VIA INTRAMOLECULAR METALLOPHTHALOCYANINE FORMATION AND CHARACTERIZATION OF THEIR NANOGRAPHENE-BASED COMPOSITES - ZEBARI, OSAMA ISMAIL HAJI (Fırat Üniveristesi, 2024)
Bir öncü kopolimer olarak poli[metil metakrilat-co-4-(4-vinilbenzil)oksi) ftalonitril][VBOPN]'dan metal (çinko ve kobalt) ftalosiyanin'in (SCP-MPc) molekül içi oluşumu yoluyla tek zincirli polimer molekülü 140-150 oC'de seyreltilmiş sikloheksanol koşullarında sentezlendi. VBOPN ile MMA'ın kopolimeri atom transfer radikal polimerizasyonu (ATRP) yöntemiyle hazırlandı. Ftalonitril yan grupları olan bir öncü kopolimerden metal ftalosiyaninler molekül içi makrosiklizasyon reaksiyonuyla hazırlandı. Tekli zincir polimerde molekül- deki çinko ve kobaltlı ftalosiyaninler FT-IR ve UV/Vis spektroskopisi kullanılarak doğrulandı. Nanografen katkılı SCP-MPc matrisli nanokompozitler ağırlıkça %6 nanografen kullanarak hazırlandı. Nanokompozitlerin; termal, elektriksel, dielektrik ve optik özellikleri araştırıldı. SCP-MPc/NG %6 w% nanokompozitinin dielektrik sabiti, dielektrik kaybı ve elektrik iletkenliği gibi dielektrik ve elektrik özellikleri sıcaklıkla artış gösterdi. DC iletkenlik çalışmaları sıcaklığa bağlı olup dc iletkenliğinin aktivasyon enerjisi ile ilişkili Arrhenius eşitliğine uyarak, sıcaklık-dc iletkenlik grafiğinin I. ve II bölgeleri için Ea değerleri sırasıyla 0.345 eV ve 0.275 eV olduğu belirlendi. SCP-MPc/NG %6 (ağırlıkça)'nin optik bant aralığı ve optik sabitleri (kırılma indeksi, dielektrik sabitinin gerçek değeri) ölçüldü. Reflektans ölçümleri 400-900 nm aralığında incelendi. Bu spektrumlar kullanılarak kompozitin doğrudan bant aralığı ve kırılma indisi belirlendi. Doğrudan bant aralığı; SCP-ZnPc ve SCP-CoPc için sırasıyla 2.7 eV ve 2.89 eV olarakbelirlendi.

The single-chain polymer molecule through the intramolecular formation of metal (zinc and cobalt) phthalocyanine (SCP-MPc) from poly[methyl methacrylate-co-4-(4-vinylbenzyl)oxy)phthalonitrile] [VBOPN] as a precursor copolymer under diluted conditions of cyclohexanol at 140-150 oC. Atom transfer radical polymerization (ATRP) and intramolecular macrocyclization reactions were used to make metal phthalocyanines from a precursor copolymer with phthalonitrile pendant groups. The structure of zinc and cobalt phthalocyanines within a single chain molecule was confirmed using FT-IR and UV/Vis spectroscopy techniques. Nanographene-based SCP-MPc nanocomposites were prepared and were explored for their thermal, electrical, dielectric, and optical properties. The electrical and dielectric properties such as dielectric constant, dielectric loss, and alternating (ac) and direct current (dc) conductivity of SCP-MPc/NG 6 wt % nanocomposite increased with temperature. The dc conductivity studies were temperature-dependent and obey Arrhenius's relation with the activation energy of dc conduction, Ea values for I. and II. regions were 0.345 eV and 0.275 e.V, respectively. The optical band gap and optical constants (refractive index, real of the dielectric constant) of the SCP-MPc/NG 6 w% were measured. Reflectance spectra were studied at the range of UV-vis-NIR in wavelength range of 400-900 nm. The direct band gap and refractive index of the composites were determined using these spectra. The direct band gap SCP-ZnPc and SCP-CoPc was found to be 2.7 eV. and 2.89, respectively
Molekül içi metaloftalosiyanin oluşumu yoluyla tek zincirli metil metakrilat kopolimerlerinin hazırlanması ve nanografen esaslı
Keywords: Kimya